1964
DOI: 10.1039/jr9640001012
|View full text |Cite
|
Sign up to set email alerts
|

196. Nitrido- and arylimido-complexes of rhenium

Abstract: Rhenium(v) in combination with tertiary phosphines as ligands has a strong tendency to form multiple bonds to nitrogen. Three new series of complexes containing such bonds, of the types [ReX,(NAr) (PRJJ, [ReNX,(PR,),], and [ReNX,(PR,),] (X = halogen, Ar = aryl, R = alkyl or aryl), are described. Imido-complexes are obtained by the reaction of the arylamine on the complexes [ReOX,(PR,),] or [ReOX,(OEt) (PR,),], and the nitrido complexes by hydrazine dihydrochloride reduction of potassium per-rhenate in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
9

Year Published

1967
1967
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 0 publications
4
80
0
9
Order By: Relevance
“…The Re-N bond distance of 1.726 (6)A is at the longer limit of the range of the values if compared with 1.709 (4) and 1.690 (5)A in [ReC13(NC6H4OCH3)- (PEt2Ph)2] and [ ReCIa(NC6H4COCH3)(PEt2Ph)2] (Bright & Ibers, 1968), and with 1.685 (ll)A in [ReC13(NCH3)(PEtPh2) 2] (Bright & Ibers, 1969). It was proposed that the formal double Re-N bond in these compounds has considerable triple-bond character (Chatt, Garforth, Johnson & Rowe, 1964). Slightly shorter distances were found in nitrido complexes: 1.660 (8) …”
Section: Selected Ranges Bond Lengths (/K) and Angles (0) And Of Bomentioning
confidence: 99%
“…The Re-N bond distance of 1.726 (6)A is at the longer limit of the range of the values if compared with 1.709 (4) and 1.690 (5)A in [ReC13(NC6H4OCH3)- (PEt2Ph)2] and [ ReCIa(NC6H4COCH3)(PEt2Ph)2] (Bright & Ibers, 1968), and with 1.685 (ll)A in [ReC13(NCH3)(PEtPh2) 2] (Bright & Ibers, 1969). It was proposed that the formal double Re-N bond in these compounds has considerable triple-bond character (Chatt, Garforth, Johnson & Rowe, 1964). Slightly shorter distances were found in nitrido complexes: 1.660 (8) …”
Section: Selected Ranges Bond Lengths (/K) and Angles (0) And Of Bomentioning
confidence: 99%
“…The second type of complex, (2), investigated by Chatt et al (1)(2)(3) showed a strong band at -1800 cm-' in the infrared spectrum which was ascribed to v,,, of the acetylene coordinated to the metal. AvC,, was much larger here and Chatt et al suggested (a), that the bonding of the acetylene to the metal (formally Pt(0)) was much stronger in (2) and (b), that in (2) the acetylene was coplanar (or nearly so) with the two P atoms and the ~t .…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3) deduced that the acetylenes were relatively weakly bonded to the metal, their criterion being Av,,, (v,,,(free acetylene) -v,,,(complexed acetylene)). In most disubstituted acetylenes v,,, occurs between 2190 and 2260 cm-' (1), in these complexes it varied from about 1994 to about 2046 cm-' The decrease in frequency observed, of about 200 cm-', was therefore comparable to that observed on complexing olefins to Pt(I1) in complexes such as Zeise's salt, KPtC,H4C13 (-150 cm-').…”
Section: Introductionmentioning
confidence: 99%
“…In were prepared according to the literature methods. 19 Instrumentation IR spectra were recorded on a Nicolet Magna 560 spectrophotometer in the spectral range 4000-400cm −1 with the samples in form of KBr pellets. The 1 H NMR, 13 C NMR and 31 P NMR spectra were recorded (298 K) on Bruker Avance 500 NMR spectrometer at a resonance frequency of 500 MHz for 1 H NMR spectra, 125 MHz for 13 C NMR spectra and 162 MHz for 31 P NMR using DMSO-d 6 as solvent and TMS as an internal standard.…”
Section: Discussionmentioning
confidence: 99%